The decoration of the Pronaos of Petosiris’ tomb: themes, scenes, styles and techniques - Sales, José das Candeias (2018)
The tomb of Petosiris at Tuna el-Gebel was discovered in late 1919 and was immediately and methodically excavated until March 8, 1920 by Gustave Lefebvre. Since then, it has been recognised as having exceptional value for the history of art of the fourth century BC, when indigenous schools produced their last copies and when the first manifestations of Greek art appeared in Egypt. The internal decoration of the pronaos of this tomb displays the strong Greek influence on the style and on the art of coloured reliefs. At the same time, it portrays themes and scenes similar to the decor of the Memphite tombs from the Old Kingdom and the Theban tombs from the New Kingdom. The depicted topics denote, therefore, a remarkable historical continuity that will be dealt with this paper, within a framework of intrinsic similarities and originalities.